A Rare Case of Retroperitoneal Isolated Enteric Duplication Cyst with Malignant Transformation. (28th October 2020) - Alhamar, M; Alkamachi, B; Jaratli, H; Shah, R
Abstract: Introduction/Objective: Isolated enteric duplication cysts (IEDC) are rare congenital abnormalities that do not have a communication with the normal intestinal lumen. They are usually recognized before the age of 2 years. They are rarely encountered in adults and very seldom undergo malignant change. These cysts are predominantly located within the abdominal cavity. They histologically demonstrate gastrointestinal mucosal lining and smooth muscle in the wall. Methods: We report a case of a 45-year-old African American female who was evaluated for a pain in the left-sided abdomen and pelvis. Magnetic resonance imaging revealed a large multilocular cystic retroperitoneal mass, extending into the left iliac fossa and anteriorly displacing the colon. No other mass lesion was radiologically identified. The main radiologic impression was sarcoma. A biopsy was performed, and a pathologic diagnosis of adenocarcinoma was established with a consideration of primary retroperitoneal mucinous cystadenocarcinoma. An en bloc surgical resection of the retroperitoneal mass with adjacent segment of the descending colon was accomplished. Gross examination revealed an 11 x 5 x 4 cm cystic mass, containing a necrotic fluid and adherent to a 4 cm long segment of descending colon. Microscopically, the mass was lined by neoplastic cells arranged into tubules, villi and glands. Areas of necrosis were present. The wall of the cystic mass showed extensive hyalinized fibrosis and focal invasion. The neoplastic cells had positive immunoreactivity for CK7, CK20 and CDX2, but were negative for PAX8, PR and ER. Desmin immunostain and trichrome special stain highlighted a focus of smooth muscle bundle within the wall of the mass. These findings led to the pathologic diagnosis of adenocarcinoma arising in retroperitoneal IEDC. Conclusion: In conclusion, we present this case because of its unusual presentation and location. Recognition of this entity and its rare malignant potential is important as it can pose a diagnostic challenge to pathologists.